2020
DOI: 10.21608/mjab.2020.169568
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Lupine and Fenugreek Seeds That Grow in Egypt

Abstract: Main chemical composition, bioactive constituents and antioxidant activity of Egyptian lupine and fenugreek seeds were investigated. The obtained resultsshowed that white lupine seeds have higher amount of carbohydrate and ash than that in the other seeds. Meanwhile yellow lupine seeds showed the highest percentage of fibers among all tested seeds, while fenugreek seeds were characterized by large amount of crude protein, oil and moisture comparing with both kinds of lupine seeds. On the other side, analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A comparative analysis revealed that the observed disparities in the functional attributes of wheat durum, fenugreek, and white lupine can be attributed to dissimilarities in the amino acid compositions of this food source (Kumari et al, 2022). Elkadousy et al (2020) conducted an evaluation of protein quality in fenugreek and other legumes, including white lupine. Their findings indicate that white lupine had a greater protein content compared to fenugreek.…”
Section: Protein and Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative analysis revealed that the observed disparities in the functional attributes of wheat durum, fenugreek, and white lupine can be attributed to dissimilarities in the amino acid compositions of this food source (Kumari et al, 2022). Elkadousy et al (2020) conducted an evaluation of protein quality in fenugreek and other legumes, including white lupine. Their findings indicate that white lupine had a greater protein content compared to fenugreek.…”
Section: Protein and Amino Acidsmentioning
confidence: 99%
“…Elkadousy et al. ( 2020 ) conducted an evaluation of protein quality in fenugreek and other legumes, including white lupine. Their findings indicate that white lupine had a greater protein content compared to fenugreek.…”
Section: Nutritional Composition Of Fenugreek Seedsmentioning
confidence: 99%
“…In most parts of the world, lupine and millet have traditionally been used primarily as foodstuffs, and interest in the nutritional values of lupine and millet as food ingredients have increased as people have become more aware of their health benefits (Thambiraj et al, 2015). In addition, lupine (Lupinusalbus L.) contains a variety of carbohydrates, proteins, fats, vitamins, minerals, and other essential nutrients, as well as abundant phytochemicals, which are associated with antioxidant properties and inhibit the action of malignant cell proliferation Devi et al (2014) and Elkadousy et al (2020). Proso millet contributes to the human diet due to its high levels of calcium, iron, zinc, lipids, and high-quality proteins.…”
Section: Introductionmentioning
confidence: 99%